The Effect of Organizational Culture, Leadership, Knowledge Management Innovation, and Organizational Performance on Work Motivation - Wahyudi Wahyudi; Denok Sunarsi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesian manufacturing companies face intense global competition, requiring strong organizational strategies to enhance performance and remain competitive. This study aims to analyze the influence of organizational culture, transformational leadership, and knowledge management innovation on organizational performance, with work motivation as an intervening variable, in Indonesian manufacturing companies. The research seeks to understand how these factors interact to drive success in a dynamic market. A quantitative approach was employed, using a survey method with a questionnaire distributed to 300 employees selected through stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3.0 software. The findings show that organizational culture and knowledge management innovation have significant positive effects on performance, with path coefficients of 0.892 and 0.641, respectively. Transformational leadership has a negative effect on performance, with a path coefficient of -0.553, possibly due to cultural or structural mismatches. Organizational performance strongly affect on work motivation, with a path coefficient of 0.882. In conclusion, fostering a positive organizational culture and effective knowledge management innovation enhances performance, while leadership strategies need adaptation to local contexts. These insights guide managers in improving competitiveness and suggest future research into leadership dynamics in Indonesian manufacturing.